2017
DOI: 10.1016/j.rmed.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of systemic inflammation, adiposity, and metabolic dysregulation with asthma burden among Hispanic adults

Abstract: Rationale Obesity-related asthma is associated with higher disease burden than normal-weight asthma among Hispanics. Adiposity, metabolic dysregulation, and inflammation are all implicated in pathogenesis of obesity-related asthma, but their independent contributions are poorly understood. Objective To examine the independent contributions of body fat distribution, metabolic abnormalities and inflammation on asthma symptoms and pulmonary function among Hispanics. Methods Participants of the Hispanic Commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…There are bidirectional causal connections between inflammation in the lung and non-specific inflammatory markers that creates an association between asthma and obesity [ 32 ]. The mean BMI of this group of patients was at the bottom of the range normally considered obese and BMI correlated significantly GSQ-A consistent with the hypothesis that the extra-pulmonary symptoms are linked to nonspecific inflammation [ 33 , 34 ]. Nonspecific inflammation is linked to many other biological abnormalities through a network of biological causal influence [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…There are bidirectional causal connections between inflammation in the lung and non-specific inflammatory markers that creates an association between asthma and obesity [ 32 ]. The mean BMI of this group of patients was at the bottom of the range normally considered obese and BMI correlated significantly GSQ-A consistent with the hypothesis that the extra-pulmonary symptoms are linked to nonspecific inflammation [ 33 , 34 ]. Nonspecific inflammation is linked to many other biological abnormalities through a network of biological causal influence [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…In our population of asthmatics who required any hospital readmission, more than 71% were obese or overweight, but this is not associated with the incidence of hospital readmissions. Our results are in agreement with the other authors who did not observe a relationship between obesity and exacerbations or with the control of the asthma [8,16,21,[29][30][31], although it was different from other studies where we showed a poorer control of asthma or increase in the incidence of the exacerbations with obesity [13][14][15]19,20,[32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 80%
“…Excess visceral/ectopic fat has been linked to insulin resistance, dyslipidemia, upregulated proinflammatory cytokines including tumor necrosis factor-a and interleukin-6, and decreased adiponectin (55). Insulin resistance has been reported as an effect modifier of the obesity-asthma association among U.S. children (56) and adults (57), and dyslipidemia has been associated with asthma symptoms and lower lung function among overweight and obese adults with asthma, independent from general or truncal adiposity (58). In our analysis, including homeostasis model assessment-estimated insulin resistance and/or total cholesterol/high-density lipoprotein cholesterol in the regression models rendered the association between dual-energy X-ray absorptiometry trunkpredominant adiposity and asthma among women nonsignificant.…”
Section: Original Researchmentioning
confidence: 99%